Deletion of PHO13 improves aerobic l-arabinose fermentation in engineered Saccharomyces cerevisiae. (1st December 2019) - Ye, Suji; Jeong, Deokyeol; Shon, Jong Cheol; Liu, Kwang-Hyeon; Kim, Kyoung Heon; Shin, Minhye; Kim, Soo Rin
Abstract: Pentose sugars are increasingly being used in industrial applications of Saccharomyces cerevisiae. Although l -arabinose is a highlighted pentose that has been identified as next-generation biomass, arabinose fermentation has not yet undergone extensive development for industrial utilization. In this study, we integrated a heterologous fungal arabinose pathway with a deletion of PHO13 phosphatase gene. PHO13 deletion increased arabinose consumption rate and specific ethanol productivity under aerobic conditions and consequently depleted sedoheptulose by activation of the TAL1 gene. Global metabolite profiling indicated upregulation of the pentose phosphate pathway and downstream effects such as trehalose accumulation and downregulation of the TCA cycle. Our results suggest that engineering of PHO13 has ample potential for arabinose conversion to ethanol as an industrial source for biofuels.